The Oxford Handbook of the Philosophy of Consciousness - Kriegel, Uriah (Oxford University Press, 2020)
This book provides a panoramic view of the state of the art in current philosophical research on consciousness. Featuring some of the most prominent contributors to the field, it explores (1) the wide range of types of consciousness there may be, (2) the many psychological phenomena with which consciousness interacts, and (3) the various views concerning the ultimate relationship between consciousness and the physical reality.